THROMBOCYTOPENIA - A CHALLENGE FOR PEDIATRIC EMERGENCY DEPARTMENTS - Daniela Pop; Helen Emilsson; Daniela Dreghiciu; Lucia Cinezan (Amaltea Medical Publishing House, 2019)
Objectives. This study aimed to find the most frequent causes of thrombocytopenia in patients who come to the Pediatric Emergency Department and to evaluate the importance of the investigations and immediate treatment options available in the Emergency Department for the final diagnosis. Methods. The study included 73 pediatric patients (aged two months to 16 years) with thrombocytopenia evaluated in the Pediatric Emergency Department in 6 years. The final diagnosis of the patients presenting with thrombocytopenia in the Pediatric Emergency Department was recorded. We assessed the clinical characteristics and findings of the investigations of the patients diagnosed with immune thrombocytopenic purpura (ITP). Results. Most of the patients were diagnosed with sepsis (40%). The second most frequent diagnosis was ITP (34%). Values of the platelets recorded in patients with ITP were between 1,000 and 87,000 and 14/25 (56%) of the patients with values lower than 20,000/mm3. Most of the patients with ITP received i.v. immunoglobulin. Conclusions. ITP and sepsis were the leading causes of thrombocytopenia in children in the Pediatric Emergency Department in our hospital. The suspicion of malignant hematological disorders was raised based on the data from the patient's medical history and the findings in the physical exam. Treatment with i.v. immunoglobulin in patients with ITP should only be used when patients associate active hemorrhage. The conclusions of this study allowed us to establish a protocol for the investigation and treatment of patients with ITP.